2015
DOI: 10.1039/c5nj00058k
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt oxide hollow nanoparticles as synthesized by templating a tri-block copolymer micelle with a core–shell–corona structure: a promising anode material for lithium ion batteries

Abstract: Cobalt oxide hollow nanospheres fabricated by core–shell–corona micelle of poly(styrene-block-methylacrylate-block-ethyleneglycol) in aqueous solution show good electrochemical properties for lithium batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…As shown in Figure , the powder X‐Ray Diffraction (PXRD) spectrum for the Co 3 O 4 @Al 2 O 3 /SiO 2 shows alumina‐silica peaks overlapping the cobalt‐oxide signals. However, on closer look the peaks (2θ) at 19.2, 31.3, 36.8, 44.8, 59.2, and 65.2 in Figure match the JCPDS card no: 073–1701 file, indicating Co 3 O 4 as the cobalt species . Figure shows the XPS spectrum of Co 3 O 4 @Al 2 O 3 /SiO 2 .…”
Section: Resultssupporting
confidence: 52%
“…As shown in Figure , the powder X‐Ray Diffraction (PXRD) spectrum for the Co 3 O 4 @Al 2 O 3 /SiO 2 shows alumina‐silica peaks overlapping the cobalt‐oxide signals. However, on closer look the peaks (2θ) at 19.2, 31.3, 36.8, 44.8, 59.2, and 65.2 in Figure match the JCPDS card no: 073–1701 file, indicating Co 3 O 4 as the cobalt species . Figure shows the XPS spectrum of Co 3 O 4 @Al 2 O 3 /SiO 2 .…”
Section: Resultssupporting
confidence: 52%
“…14 In the case of ABC triblock terpolymers, even further design criteria can be accomplished and well-defined structures of different morphology featuring core, shell and corona layers can be fabricated and used as potential drug delivery vehicles. [15][16][17][18] We have recently shown that multicompartment micelles from polybutadiene-block-poly(methacrylic acid)-block-poly(N,N-dimethylaminoethyl methacrylate) (BMAAD) undergo structural rearrangements within a relatively narrow pH regime (5-7) and thus are promising carriers for the transfection of pDNA into both adherent cells and cells in suspension. 19 To enhance flexibility and improve control over composition, charge and charge density within coreshell-corona micelles, we developed a platform approach based on co-assembly of polyether-based ABC triblock terpolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2s hows the powder X-Ray Diffraction (PXRD) spectrum for Co 3 O 4 @Al 2 O 3 /SiO 2 .T he XRD spectrum contains alumina-silica peaks overlappingt he cobalt-oxides ignals. [28] To further affirm the elemental oxidation states of cobalti n the preparedm aterial, XPS analyses were performed. [28] To further affirm the elemental oxidation states of cobalti n the preparedm aterial, XPS analyses were performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, on closer look, the peaks (2q)a t1 9.2, 31.3, 36.8, 44.8, 59.2, and 65.2 o in Figure 2m atch the JCPDS card no:0 73-1701 file, indicating Co 3 O 4 as the cobalt species. [28] To further affirm the elemental oxidation states of cobalti n the preparedm aterial, XPS analyses were performed. As shown in Figure 3A,t he binding energy peaks at 780.8 and 796.5 eV correspond to the Co 2p 3/2 and Co 2p 1/2 core levels, respectively,c learly showing that cobalt is present in its oxide form (Co 3 O 4 ).…”
Section: Resultsmentioning
confidence: 99%